Hubungan Latihan Gerak Dasar Tari Tradisional Gaya Surakarta Dengan Keseimbangan Dinamis Remaja Putri Usia 14 - 16 Tahun - Kusumaningrum, Pungky Widayanti; , Maskun Pudjianto, SMPh., S.Pd., M.Kes; , Dwi Kurniawati, S.ST.F (2016)
Background: Surakarta traditional dance is a dance style that uses motion as the media said. Dance movements were refined and given an aesthetic element. In dancing, dynamic balance is necessary, as it helps the dancer moves in a balanced manner and can regulate body movement. Purpose: To determine the relationship between the basic movement exercises Surakarta style of traditional dance with a dynamic balance of young women aged 14-16 years. Aim of Research: For information for the traditional dancers, that balance is needed in dancing, especially the dynamic balance, so that the dancers can make efforts to improve the dynamic balance. Research Methods: The study was observational with cross sectional approach. The sampling technique used purposive sampling, as many as 123 respondents. Measuring instrument studies using Modified Bass Test. Statistical test used was chi-square. Result of research: Statistically dynamic balance level of young women aged 14-16 years showed a p-value of 0.486 or probability (significance)> 0.05. Conclusion: There is no relationship between the basic movement exercises Surakarta style of traditional dance with a dynamic balance of young women aged 14-16 years. Keywords: Basic Motion Style Traditional Surakarta Dance, Dynamic balance.